1986
DOI: 10.1111/j.1365-2133.1986.tb06237.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of psoriasis with topical application of active vitamin D3 analogue, 1α, 24-dihydroxycholecalciferol

Abstract: We treated 11 psoriatic patients with topical 1 alpha,24-dihydroxycholecalciferol, a new synthetic analogue of active vitamin D3. In 10 of 15 tests the lesions cleared completely within 1-4 weeks, although some relapses occurred shortly after cessation of treatment. There were no side-effects. We suggest that 1 alpha, 24(OH)2D3 merits further investigation as a potentially useful topical therapy for psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(30 citation statements)
references
References 6 publications
0
30
0
Order By: Relevance
“…Pharmacological doses of 1,25(OH) 2 D 3 induce hypercalcemia when administered systemically, which is a significant obstacle when considering its clinical application. However tacalcitol ointment and cream preparations have been prescribed successfully for the treatment of psoriasis [15,16,31]. In this case, administration via the topical route delivers a higher concentration of the drug to epidermal lesions [32] than could be achieved using a systemic route.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological doses of 1,25(OH) 2 D 3 induce hypercalcemia when administered systemically, which is a significant obstacle when considering its clinical application. However tacalcitol ointment and cream preparations have been prescribed successfully for the treatment of psoriasis [15,16,31]. In this case, administration via the topical route delivers a higher concentration of the drug to epidermal lesions [32] than could be achieved using a systemic route.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunctional growth and differentiation of epidermal cells combined with an inflammatory immune response are key elements in the development of psoriasis [7]. The demonstrated effects of calcitriol on these factors, therefore, led to its investigation for the control of psoriasis and it has now been shown that calcitriol and a number of analogues, principally calcipotriol, are effective therapies for psoriasis [3, 8, 9, 10, 11]. …”
Section: Introductionmentioning
confidence: 99%
“…1.24 dihydroxycholecalciferol appeared to be effective when used topically (27), but this compound is almost as active as calcitriol in mineral metabolism.…”
Section: Effcwymentioning
confidence: 99%